E-Module of Cost Estimating Course in Building Construction Vocational Undergraduate Program Faculty of Engineering Universitas Negeri Jakarta - Arthur, Riyan; Dwi, Riza Nur; Lenggogeni, Lenggogeni (Jurnal Ilmu Pendidikan, 2019)
This R&D aims to develop e-modules based on blended learning in the cost esti-mating course. The research used the R&D method with the 4D (four-D) model carried out through four main stages, namely define, design, development, and dissemination. The e-module development was limited only to the assessment and limited dissemination to experts or the development stage. This study used a questionnaire as a tool to test the feasibility of the instructional through expert validation and student assessment. The results obtained from Instructional experts, material, and students showed that this electronic module is suitable for use in cost estimating subject in Building Construction Vocational Undergraduate Program, Faculty of Engineering, Universitas Negeri Jakarta. However, further research is needed on the fourth stage (disseminate).